Prospective evaluation of spinal cord stimulation in refractory angina: insights from a single-center cohort - Gasimova, Nigar Z.; Paltsev, Artem A.; Zayachkovskiy, Nikita A.; Nezdorovina, Viktoriya G.; Nezdorovin, Oleg V.; Bortsova, Mariya A.; Osipova, Mariya A.; Remizov, Nikita S.; Condori Leandro, Heber Ivan; Vatian, Aleksandra S.; Lebedev, Dmitry S.; Mikhaylov, Evgeny N. (Frontiers in Cardiovascular Medicine, 2025)
BackgroundRefractory angina pectoris represents a significant clinical challenge characterized by persistent chest pain despite maximally tolerated medical therapy and optimal revascularization attempts. This study evaluates the efficacy and safety of invasive spinal cord stimulation (SCS) in patients with refractory angina.MethodsTwenty-one patients underwent neurostimulation system implantation between 2022 and 2023 (mean age 62.8 ± 7, 12 males) diagnosed with refractory angina. All patients received both chronic continuous stimulation and on-demand stimulation to alleviate anginal pain episodes. The primary endpoint was changes in the Seattle Angina Questionnaire (SAQ-19) scores. Secondary endpoints included changes in the Short Form Health Survey (SF-36), incidence of major adverse cardiovascular events, device-related complications, and nitrate use.ResultsEighteen patients completed the final follow-up. No statistically significant improvements were observed in any SAQ-19 domains. However, reductions in pain scores (41% vs. 53%, p = 0.007) and improvements in mental health scores (61% vs. 72%, p = 0.021) and physical functionating (36 vs. 52%, p = 0.017) were noted on the SF-36. Device extraction occurred in three cases (14%)—two due to pocket infection and one at the patient's request. Four lead repositioning procedures were performed (19%). Hospitalization rates significantly decreased over the one-year observation period, from 3.8 to 0.5 hospitalizations per patient (p = 0.03). Recurrent acute coronary syndrome was noted in one patient, requiring additional coronary stentings. Notably, although no significant reduction in nitrate therapy was achieved, the treatment regimen prevented any new nitrate prescriptions during the study period.ConclusionSCS did not significantly improve the primary endpoint of disease-specific quality of life (SAQ-19). However, treatment was associated with secondary benefits, including improvements in physical functionating, pain and mental health (SF-36) and a significant reduction in hospitalization rates. Complication rates were significant.